The State Hermitage Museum Collection of Casts Made from Count Poniatowski’s Engraved Gems - Dmitrieva, Elena N. (Actual Problems of Theory and History of Art, 2018)
The article is dedicated to the content of the collection of plaster casts made from Prince Stanislas Poniatowski’s engraved gems, as well as to the history and the circumstances of the receipt of the collection by the State Hermitage. The article provides previously unpublished data from the Hermitage archive, which reveal the provenance of the collection and allow to clarify its attribution. It also compares the images of Prince Poniatowski’s gems available as a part of Beazley’s archive project in Oxford with the set of casts and its accompanying handwritten catalog available in the Hermitage. This makes it possible to complement Beazley’s image database with previously unknown images. Thus, a small collection of the Hermitage impressions allows us to make a substantial contribution to the reconstruction of the once-famous collection of glyptic of S. Poniatowski.
Keywords: Hermitage; glyptics; plaster casts from engraved gems; Prince Stanislas Poniatowski; collections’ history